Periparturient blood T-lymphocyte PD-1 and CTLA-4 expression as potential predictors of new intramammary infections in dairy cows during early lactation (short communication) - Ana Cláudia Dumont Oliveira; Carolina Menezes Suassuna de Souza; Eduardo Milton Ramos-Sanchez; Soraia Araújo Diniz; Ewerton de Souza Lima; Maiara Garcia Blagitz; Robson Cavalcante Veras; Marcos Bryan Heinemann; Alice Maria Melville Paiva Della Libera; Sarne De Vliegher; Artur Cezar de Carvalho Fernandes; Fernando Nogueira Souza (BMC Veterinary Research, 2024)
Abstract Background The periparturient period in dairy cows is marked by immunosuppression which increases the likelihood of infectious disorders, particularly also mastitis. An in-depth understanding of peripartum leukocyte biology is vital for the implementation of highly successful post-partum disease prevention measures. Immune checkpoint molecules, such as programmed death 1 (PD-1) and cytotoxic T-lymphocyte antigen 4 (CTLA-4), are critical inhibitory receptors expressed on immune cells, particularly T cells, that drive immunosuppressive signaling pathways. However, the potential role of immune checkpoint molecules expression in T-cells on udder health has never been explored. Thus, the association between the occurrence of new postpartum intramammary infections (IMIs) and the expression of programmed cell death protein 1 (PD-1) and cytotoxic T-lymphocyte-associated antigen-4 (CTLA-4) on blood T-cells during the peripartum period was investigated. Results In this study, the incidence of IMIs by any pathogen in early lactation was not associated with a higher expression of PD-1 and CTLA-4 in the periparturient period. However, the incidence of IMIs by major pathogens throughout the first month of lactation was significantly associated with higher expression of PD-1 at 14 days before calving (P = 0.03) and CTLA-4 at parturition (P = 0.03) by blood T-cells. Also, the expression of CTLA-4 at D0 (P = 0.012) by T-cells was associated with the occurrence of persistent IMIs during the first month of lactation. Conclusions To our knowledge, this is the first report to investigate the expression of PD-1 and CTLA-4 by blood T-lymphocytes during the periparturient period in dairy cows and to explore their relationship with the incidence of new IMIs in the postpartum period. Thus, a comprehensive understanding of leukocyte biology during peripartum would appear to be a prerequisite for the identification of resilient dairy cows or targets innovative (immunological) non-antibiotic approaches in the transition period.